Geomorfologia, hidrografia e tectônica da folha Araçaji 1:25.000, estado da Paraíba - Silva, Ivanildo Costa da (2014)
The present research had as main objective analyze the inter-relationship between geology, relief and hydrography on the area of the letter of Araçaji 1:25.000 (sheet SB.25-Y-A-V-3- NE), and thy mutual contributions to the development of ancient geomorphological feature and also current of this region. Furthermore it had as objective verify the influence of tectonics events and neotectonics about network configuration and drainage pattern. It is understood that knowledge of geomorphological modeled of a area in a concise form on elaboration of planning directed to the most diverse purposes, as: engineering works, environmental, agricultural development, mineral exploration, among other. This consideration applies to the area of the sheet Araçaji 1:25.000, it is known that is in course, since last decade after the construction of Arua Dam, a free expansion of agricultural practices. Moreover, it is being developed in the area of study, researchers focused on mineral exploration. In this study qualitative and quantitative aspects of geomorphology and drainage network were analyzed with the aid of cartographic material produced and the application of morphometric indices. The production of cartographic material, essential for qualitative analysis, consisted mainly in the preparation of thematic maps hypsometric, clinographyc, the Digital Elevation Model (DEM) and geomorphological letter. For quantitative and neotectonic analysis were applied the morphometric indices of Slope Relationship / Extension (SRE), Reason Fund / height Valley (RFHV) and Asymmetric Factor (AF). The thematic maps and DEM were generated on the software Spring 5.2, based on data extracted from leaf Araçaji 1:25.000 by manual vectorization, such as contour lines with contour interval of 10 meters, elevation points and other elements, such as hydrography, roads and highways. The preparation of geomorphological letter was based on the methodology proposed by Ross (1992), which is based on the taxonomic units of relief. The results shows that there are various anomalies in the area of the sheet Araçaji 1:25,000, such as altimetry with quotes at average of the region on the area of the geological unit of felsic volcanic rock Itapororoca, which was shown to have been affected by faults and compressive stresses shown in folded rocks with aspects of tectonic breccias, and other anomalies such as: strong inflections, straight channels and modified the drainage network influenced mainly dextral strike-slip faulting shown by field and by the local geological framework standards. Combined with qualitative analysis, the values obtained with the application of morphometric indices showed that the drainage network of the study area was also affected by neotectonic events. It follows therefore, that the combined qualitative analysis to quantitative analysis in geomorphological studies and drainage network brought reliable results that are complementary, and have been instrumental in detecting the activity of neotectonic events in geomorphological modeling and drainage network leaf area Araçaji 1:25.000